Synthesis of alginate derivative via the Ugi reaction and its characterization. (20th January 2016) - Yan, Huiqiong; Chen, Xiuqiong; Li, Jiacheng; Feng, Yuhong; Shi, Zaifeng; Wang, Xianghui; Lin, Qiang
Highlights: The amphiphilic alginate derivative (Ugi-Alg) was prepared via the Ugi four-component reaction. The crystal structure change occurred during the synthesis of Ugi-Alg. Ugi-Alg displays higher thermal stability in comparison with pristine alginate. Ugi-Alg exhibits good amphiphilic functionality similar to the classic surfactant. Ugi-Alg could form stable self-aggregated micelle in the aqueous media. Abstract: In this research, the systematic evaluation of fundamental properties of the alginate derivative (Ugi-Alg) synthesized by the Ugi reaction is presented. The structure of Ugi-Alg with the degree of substitution of 23.24% was confirmed by FT-IR and 1 H NMR spectrometers. The X-ray diffraction (XRD) results indicate the amorphous structure and the crystal structure change of Ugi-Alg, which is possibly ascribed to the destruction of inter- and intra-molecular hydrogen bonding interactions during the Ugi reaction. From thermal gravimetric analysis (TGA) and fluorescence spectrophotometer, Ugi-Alg shows high thermal stability and good amphiphilic functionality with the critical aggregation concentration of 0.07 g/L in 0.15 mol/L aqueous NaCl solution. Transmission electron microscope (TEM) image and dynamic light scattering (DLS) reveal that stable Ugi-Alg self-aggregated micelle with the average size of 162.3 nm and ζ potential at about −31.7 mV could form in the aqueous media, which presents tremendous potential in pharmacology and tissue engineering.